Gains in native species promote biotic homogenization over four decades in a human‐dominated landscape. (7th October 2013) - McCune, Jenny L.; Vellend, Mark
Summary: A long‐term perspective is needed to understand how disturbance is affecting plant communities in human‐dominated landscapes. Increased human disturbance often results in declining local native species richness, gains in exotic species and a decline in beta diversity. However, it is far from certain whether a general decline in plant diversity is occurring across all disturbed landscapes, and knowledge gaps remain concerning how the spread of exotic species influences beta diversity over long time‐scales. We resurveyed 184 vegetation plots in three broad vegetation types on southern Vancouver Island, Canada, originally surveyed in the late 1960s. This landscape has experienced a high degree of human disturbance over the past 40 years due to urbanization. We examined changes in total diversity, local diversity and beta diversity over time. We also compiled information on the traits of each species and tested for correlations between traits and plant species success over four decades. We found striking increases in local and total plant species richness driven by both native and exotic species. The most successful species tended to be exotic, disturbance tolerant, shade tolerant and shrubs. Biotic homogenization occurred, but not as a result of exotic species colonization, instead being significantly correlated with gains in native species. The loss in beta diversity has resulted in a shrinking of the gradient of vegetation types, blurring the distinction between them. Synthesis . Our study shows that human‐mediated disturbance is the dominant driver of plant community changes, but the net result has actually been an increase in richness, for each plot and for all plots pooled, and for both natives and exotics, despite a decline in variability among plant communities on the landscape. Contrary to conventional definitions of biotic homogenization, this decline in beta diversity was not correlated with the spread of exotic species, but with the colonization of common, disturbance‐tolerant natives. Abstract : We resurveyed 184 vegetation plots on southern Vancouver Island originally surveyed in the late 1960s. We found an increase in richness, for each plot and for all plots pooled, but a decline in variability among plant communities. This decline in beta diversity was not correlated with the spread of exotic species, but with the colonization of common, disturbance‐tolerant natives.